Spoken from the front real voice from the Battlefields of Afghanistan - McNab, Andy 1959- (Bantam Press, 2009)
Tells the stories of what the author describes as 'modern-day heroes fighting modern-day wars'. This title recounts the courage and hardship of British servicemen and supports staff as they have faced the difficulties posed by the conflict in Afghanistan.